Lacking ARHGAP25 mitigates the symptoms of autoantibody-induced arthritis in mice - Domonkos Czárán; Péter Sasvári; Ádám István Horváth; Ádám István Horváth; Krisztina Ella; Ágnes Réka Sűdy; Éva Borbély; Éva Borbély; Kitti Rusznák; Kitti Rusznák; Boldizsár Czéh; Boldizsár Czéh; et al. (Frontiers in Immunology, 2023)
ObjectiveDespite intensive research on rheumatoid arthritis, the pathomechanism of the disease is still not fully understood and the treatment has not been completely resolved. Previously we demonstrated that the GTPase-activating protein, ARHGAP25 has a crucial role in the regulation of basic phagocyte functions. Here we investigate the role of ARHGAP25 in the complex inflammatory process of autoantibody-induced arthritis.MethodsWild-type and ARHGAP25 deficient (KO) mice on a C57BL/6 background, as well as bone marrow chimeric mice, were treated i.p. with the K/BxN arthritogenic or control serum, and the severity of inflammation and pain-related behavior was measured. Histology was prepared, leukocyte infiltration, cytokine production, myeloperoxidase activity, and superoxide production were determined, and comprehensive western blot analysis was conducted.ResultsIn the absence of ARHGAP25, the severity of inflammation, joint destruction, and mechanical hyperalgesia significantly decreased, similarly to phagocyte infiltration, IL-1β, and MIP-2 levels in the tibiotarsal joint, whereas superoxide production or myeloperoxidase activity was unchanged. We observed a significantly mitigated phenotype in KO bone marrow chimeras as well. In addition, fibroblast-like synoviocytes showed comparable expression of ARHGAP25 to neutrophils. Significantly reduced ERK1/2, MAPK, and I-κB protein signals were detected in the arthritic KO mouse ankles.ConclusionOur findings suggest that ARHGAP25 has a key role in the pathomechanism of autoantibody-induced arthritis in which it regulates inflammation via the I-κB/NF-κB/IL-1β axis with the involvement of both immune cells and fibroblast-like synoviocytes.